Strategi komunikasi media Islam alif.id dan ibtimes.id dalam penyebaran paham moderasi - Firda Dwi Aprilyawati; Nurudin Nurudin (Islamic Communication Journal, 2022)
This study aims to know the media communication strategies of Alif.id and IBTimes.id as website media with a moderate Islamic background. The approach adopted in this study is a descriptive qualitative approach. The results of this study indicated that the strategies used by the media Alif.id and IBTimes.id are the strengthening of the character and the branding of each media by using a cultural approach. Thus, Alif.id and IBTimes.id are also consistent in maintaining the quality of the Islamic missionary (da'wah) content presented through articles and readings. In addition, the publication through social media becomes an important strategy because it is able to reach a broad and fast target audience. Again, the presentation of variations in content such as events, presentations, news, and inspirational videos can also increase engagement and awareness of target audience.  As an implication, this study recommends the necessity of using media in an effort to spread the values of religious moderation in the midst of a lot of counter-productive content with universal religious spirit.***Tujuan dari studi ini adalah untuk mengetahui strategi komunikasi media Alif.id dan IBTimes.id sebagai media Islam moderat. Studi ini menggunakan pendekatan kualitatif dengan metode deskriptif. Studi menunjukkan hasil bahwa strategi yang digunakan oleh media Alif.id dan IBTimes.id, yaitu penguatan karakter dan branding media masing-masing dengan menggunakan pendekatan secara kultural. Alif.id dan IBTimes.id konsisten dalam menjaga kualitas muatan dakwah yang disajikan melalui artikel dan bacaan. Publikasi melalui media sosial menjadi strategi yang penting karena mampu menyentuh target khalayak secara luas dan cepat. Selain itu, penyajian variasi konten seperti event, sajian, berita, video inspiratif juga mampu meningkatkan ketertarikan dan keterikatan target audience. Sebagai implikasinya, studi ini menganjurkan keharusan penggunaan media dalam upaya menyebarkan nilai-nilai moderasi beragama di tengah banyaknya konten yang kontra-produktif dengan semangat keagamaan universal.